Globalization and Value Chain Analysis - A Critical Evaluation - Ramesh, H. N. (Indian Journal of Marketing, 2007)
Analysis of economic gain from the globalisation and global trade for a participating nation through value chain analysis is an eye opener for the entrepreneurs and policy makers. In the global trade context, value chain analysis provides an opportunity to determine the income distribution between and among the participating countries. This article attempts to explain the conceptual meaning and practical implication of globalisation. The importance of global value chain analysis in determining the income distribution among the value chain partners is discussed. It is also focusing on the reasons for unequal distribution of income among the participating countries.